COMPARATIVE ANALYSIS OF PHRASEOLOGICAL UNITS WITH ANTHROPONYMS IN ENGLISH AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2023)
Phraseological units of the English and Uzbek languages ​​with an anthroponym component are analyzed in the article. Expressions of the English language with a component of an anthroponym of biblical origin, as well as phraseological units from the scriptures of the Koran proper names have been included in the article.